Perancangan Corporate Identity Tito Jaya Motor Medan - Efni Ayu Anggraini efni (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Tito Jaya Motor is a small and medium business in the automotive sector, especially providing car repair and also buying and selling used cars. The increasing number of similar businesses that are developing makes the existing competition tighter. Tito Jaya Motor requires a corporate identity in order to create a distinctive feature of Tito Jaya Motor so that it can compete with other similar businesses. The purpose of this study project is to produce a corporate identity which includes a logo, dress code, and merchandise.With the design of Tito Jaya Motor's corporate identity which is applied to various media that support in enhancing the company's image, it is hoped that this can have a positive impact on Tito Jaya Motor in running its business and can be used as a reference by various parties in developing businesses, especially in the automotive sector.